Analisis Perbandingan Persepsi Kualitas Pelayanan Dan Kepuasan Konsumen Jasa Transportasi Online Di Sumatera Selatan - PUTRI, NYAYU KHAIRANI (Jurusan Akuntansi Politeknik Negeri Padang, 2020)
The purpose of this research is to compare perceptions of service quality and consumer satisfaction of online transportation services in South Sumatra, with a Case Study of Go-Jek Consumers, Go-Ride Service Users and Grab Consumers, Grabbike Service Users. This research is a comparative study. Information about the research is obtained from data collection techniques that have been carried out on research subjects, namely users of Go-Jek (GoRide) and Grab (Grabbike). The population in this study ware people who had used Go-Jek and Grab, while the study sample was 100 respondents. The Paired Sample T-Test is a data analysis technique in this study using the IBM SPSS Statistics 22 application.The results showed that there was no significant difference between Go-Ride Service Quality and Grabbike Service Quality, and there was a significant difference between Go-Ride Consumer Satisfaction and Grabbike Consumer Satisfaction.